Prevalence of head and face actinic keratosis among older community residents aged ≥60 years in Shanghai: a cross-sectional study - Dekun Song; Yang Li; Lunhui Chang; Lunhui Chang; Kai Liu; Yunwei Yang; Yunwei Yang; Zhenlin Li; Zhenlin Li; Ruiping Wang; Guolong Zhang (Frontiers in Medicine)
BackgroundActinic keratosis (AK), as a key indicator of skin cancer risk, is vital for understanding the skin health status of the elderly population. However, the epidemiological data on the prevalence of AK among community residents in Shanghai remain limited. This study aimed to investigate the prevalence of AK in older Shanghai residents and explore the associated factors.MethodsA convenience sampling method was utilized to conduct a questionnaire survey among residents aged 60 years and above in a sub-district in Shanghai from March to June 2024. Data on participants’ demographic features, medical history, lifestyle, and skin conditions were collected, and a dermoscopic examination was performed on suspicious head and facial lesions to diagnose AK. In this study, a logistic regression model was applied to explore factors associated with the development of AK, and a p value less than 0.05 was considered statistically significant.ResultsA total of 1,352 residents aged ≥ 60 years were recruited in the study, with 579 males (42.8%) and 773 females (57.2%). 79 AK cases were identified by dermoscopic examination, resulting in a prevalence rate of 5.84%. Residents diagnosed with AK in this study exhibited the following characteristics: older age, male predominance, higher rates of outdoor occupation and immunosuppressive drug use, increased prevalence of dry or mixed skin types, and lower skin health awareness. Logistic regression analysis indicated that older age was a risk factor for AK, with an odds ratio (OR) of 4.37 [95% confidence interval (CI): 1.02–18.83]. However, indoor work and good skin health knowledge were protective factors for AK, with the OR of 0.43 (95% CI: 0.24–0.77) and 0.57 (95% CI: 0.35–0.92), respectively.ConclusionAge and outdoor work are significant risk factors for AK, while a higher level of skin health knowledge was protective against AK among older residents. The findings highlight the importance of early disease screening and skin health education among community residents.